Every breath - Sparks, Nicholas (New York : Grand Central Publishing, 2018)
"Nicholas Sparks returns with his signature combination of gripping, emotionally resonant storytelling and love overcoming all odds"--
Keywords: Amyotrophic lateral sclerosis -- Fiction; Romance fiction; Large type books